Omega -slow solutions and Be star disks - Araya, I. (2017)
As the disk formation mechanism(s) in Be stars is(are) as yet unknown, we investigate the role of rapidly rotating radiationdrivenwinds in this process. We implemented the effects of high stellar rotation on m-CAK models accounting for: the shape of the star, the oblate finite disk correction factor, and gravity darkening. For a fast rotating star, we obtain a two-component wind model, i.e., a fast, thin wind in the polar latitudes and an Ω-slow, dense wind in the equatorial regions. We use the equatorialmass densities to explore Hα emission profiles for the following scenarios: 1) a spherically symmetric star, 2) an oblate shaped star with constant temperature, and 3) an oblate star with gravity darkening. One result of this work is that we have developed a novel method for solving the gravity darkened, oblated m-CAK equation of motion. Furthermore, from our modeling we finda) the oblate finite disk correction factor, for the scenario considering the gravity darkening, can vary by at least a factor of two between the equatorial and polar directions, influencing the velocity profile and mass-loss rate accordingly, b) the Hα profiles predicted by our model are in agreement with those predicted by a standard power-law model for following values of the lineforce parameters: 1.5 . k . 3, α ∼ 0.6 and δ & 0.1, and c) the contribution of the fast wind component to the Hα emission line profile is negligible; therefore, the line profiles arise mainly from the equatorial disks of Be stars.